2001
DOI: 10.1088/0953-2048/14/4/101
|View full text |Cite
|
Sign up to set email alerts
|

High intergranular critical currents in metallic MgB2superconductor

Abstract: Strong evidence for high intergranular critical current densities and large bulk magnetic flux pinning in superconducting polycrystalline MgB 2 has been observed. The presence of strongly-coupled grain boundaries in this material has been confirmed by a dramatic collapse of the magnetic hysteresis loop when a bulk specimen is ground into a fine powder and re-measured under similar conditions. Further evidence for strong intergrain links in polycrystalline MgB 2 is provided by the continuous variation of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
128
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(135 citation statements)
references
References 5 publications
5
128
0
2
Order By: Relevance
“…High transport critical current densities have been reported in MgB 2 bulk samples [2]- [4]. Due to its intermediate transition temperature, weak-link free grain boundaries [5] and low material cost, this material is interesting for potential applications such as MRI (magnetic resonance imaging) and transformers at operating temperature of 20-30K.…”
Section: Introductionmentioning
confidence: 99%
“…High transport critical current densities have been reported in MgB 2 bulk samples [2]- [4]. Due to its intermediate transition temperature, weak-link free grain boundaries [5] and low material cost, this material is interesting for potential applications such as MRI (magnetic resonance imaging) and transformers at operating temperature of 20-30K.…”
Section: Introductionmentioning
confidence: 99%
“…Transport and magnetization measurements of the upper critical field [4][5][6][7][8] and critical current density 9,10 of MgB 2 revealed properties typical for a type-II superconductor. Since crystal structure of MgB 2 consists of alternating Mg and B sheets, electronic anisotropy of this material may be expected.…”
mentioning
confidence: 97%
“…25.Sv Soon after the discovery of superconductivity in MgB 2 [1], it was found that grain boundaries do not limit the current flow in polycrystalline samples [2,3]. Thus, sintered bulk samples and wires could be prepared with critical current densities appropriate for technical applications at low magnetic fields [4].…”
mentioning
confidence: 99%
“…The resistive transition of a sintered bulk sample [3] was measured at fixed magnetic field at a current density of 2 kA/m 2 . The onset of the transition was defined at 95 % of the normal state resistance, the offset at 5 %.…”
mentioning
confidence: 99%
See 1 more Smart Citation